Differential Protection of a Three-Phase Power Transformer Using Hall Effect Current Transducer - Fathollahi Fard, Ali Asghar (2002)
In a power system, transformers and other electrical equipment need to be protected not only from short circuit, but also from abnormal operating conditions, such as over loading, and differential fault protection. The differential protection relay works on the princ1ple that in a healthy system, the current leaving a circuit is equal to the current entering the circuit. The differential protection can also be applied to a transformer (even though the primary and secondary currents are not equal), by rating the CTs according to the transformation ratio. In a power system, the differential relay should operates only in its specified protection zone, and not for out of its protection zone, when short circuit fault occurs. Differential protection zone for a transformer is in the limited zone between transformer primary side CTs and transformer secondary side CTs. If a short circuit fault occurs in this zone, then the differential relay will operate to protect transformer not to be damaged by the high circuit current. This work has been focused on construction, normal operation of differential relay and on the problem when differential relay is functioning outside of its protection zone and a way of solving the problem, further to test its function by creating faults on nearby power system. This work has shown that if the current ratio of current transducers are not matched with the current of transformer, therefore it would cause the differential relay functions even though the faults occur outside the relay protection zone.